Reconfigurable Computing: Architectures, Tools and Applications 7th International Symposium, ARC 2011, Belfast, UK, March 23-25, 2011. Proceedings - Koch, Andreas; Krishnamurthy, Ram.; McAllister, John.; Woods, Roger; El-Ghazawi, Tarek; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 7th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2011, held in Belfast, UK, in March 2011. The 40 revised papers presented, consisting of 24 full papers, 14 poster papers, and the abstracts of 2 plenary talks, were carefully reviewed and selected from 88 submissions. The topics covered are reconfigurable accelerators, design tools, reconfigurable processors, applications, device architecture, methodology and simulation, and system architecture.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Computer simulation; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Computation by Abstract Devices; Programming Techniques; Simulation and Modeling